2017
DOI: 10.18632/oncotarget.17889
|View full text |Cite
|
Sign up to set email alerts
|

6-mercaptopurine promotes energetic failure in proliferating T cells

Abstract: The anticancer drug 6-mercaptopurine (6-MP) inhibits de novo purine synthesis and acts as an antiproliferative agent by interfering with protein, DNA and RNA synthesis and promoting apoptosis. Metabolic reprogramming is crucial for tumor progression to foster cancer cells growth and proliferation, and is regulated by mechanistic target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK) as well as the oncogenes Myc and hypoxia inducible factor 1α (HIF-1α). We hypothesized that 6-MP impacts metabolic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…In this context, mTOR seems therefore to drive cells toward a more sustained metabolism, with higher fluxes of glycolysis followed by an OXPHOS upregulation. An indirect evidence has in fact been reported by Fernández-Ramos et al, who observed that 6-mercaptopurine inhibits mTOR through AMPK activation, consequently reducing glucose and glutamine consumption by T leukemia cells [97]. In Table 2, the metabolic effects of mTOR inhibition in B-and T-ALL are reported.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 82%
“…In this context, mTOR seems therefore to drive cells toward a more sustained metabolism, with higher fluxes of glycolysis followed by an OXPHOS upregulation. An indirect evidence has in fact been reported by Fernández-Ramos et al, who observed that 6-mercaptopurine inhibits mTOR through AMPK activation, consequently reducing glucose and glutamine consumption by T leukemia cells [97]. In Table 2, the metabolic effects of mTOR inhibition in B-and T-ALL are reported.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 82%
“…Tested in a randomized trial in DMD patients as an alternative immunosuppressant, AZA did not exert any physical benefit when compared to prednisone 29 , although muscle biopsies showed comparable immunohistological ameliorations 30 . While the primary mechanism underlying AZA pharmacological activity can be imputed to its interference with DNA synthesis 31 , 32 , alternative biological processes have been implicated in the drug mechanism of action 19 , 20 , 33 – 37 .…”
Section: Discussionmentioning
confidence: 99%
“…6-MP has been widely used for the clinical treatment of IBD [23] and recent studies have given evidences for direct anti-inflammatory properties of 6-MP [25,28,48]. In particular, 6-MP was shown to inhibit the induced expression of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences have been provided in support of direct anti-inflammatory functions of 6-MP, occurring independently of its cytostatic activity. Indeed, 6-MP has been shown to promote T-cell cycle arrest and apoptosis in the Jurkat human T lymphocyte cell line [25]. Furthermore, 6-MP regulates the transcriptional activities of the orphan nuclear receptors NR4A1-3, which are involved in the regulation of inflammatory reactions and neoplasia [26,27].…”
Section: Introductionmentioning
confidence: 99%